AN ANALYSIS OF THE USE OF MAKE A MATCH TECHNIQUE IN INCREASING VOCABULARY MASTERY FOR JUNIOR HIGH SCHOOL STUDENTS - Simanjuntak, Fernando Saputra; Prawati, Atni; Syafrianti, Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This descriptive research was aimed to find out the effectiveness of Make a Match Technique in increasing students’ vocabulary mastery for junior high school. In this research the data were taken from seven references including journals and previous research studies that published in 2014 – 2020. The data were analyzed in two processes: descriptive analysis and content analysis. The result of the data analysis showed that the researcher of the seventh data sources had the similarities of research questions/objectives, their research questions/objectives related to the objective of the research in this research which is to find out the effectiveness of Make a Match Technique in increasing vocabulary mastery. There were Classroom Action Research, Experimental Research and Qualitative Descriptive found in the seventh data sources as the research design. Besides, the similarities findings found from the seventh data sources was that Make a Match Technique significantly improve students’ vocabulary mastery. Thus, it can be concluded that Make a Match Technique was effective in increasing students’ vocabulary mastery for junior high school studentsKey Words: Make a Match Technique, Vocabulary Mastery, Analysis